Level of professional pressures during the use of e-learning teaching method among teachers of the Faculties of Physical Education and Sports Sciences in Baghdad - Ismail Adham, Sahab; Al-Zuhairi, Najla Abbas (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to identify the reality of the level of professional pressures during the use of e-learning among teachers of the Faculties of Physical Education and Sports Science in Baghdad. A cross sectional study was carried out and the descriptive approach was adopted in a survey method on a sample of 120 faculty members of the Faculties of Physical Education and Sports Sciences in the Universities of Baghdad Governorate (Baghdad Al-Jadriya, Baghdad for Girls, Al-Mustansiriya). The two researchers used the “Occupational Stress Scale” as the main instrument for measurement in the study and it was applied to the study sample for a period from 18/04/2021 until 27/05/2021. The Statistical Package for Social Sciences (SPSS, version 26) was used for data analysis. The results showed that the members of the teaching staff in the Faculties of Physical Education and Sports Sciences have a high level of occupational pressure (p < 0.05), with an increase of the undesirable level of pressure on relationships and communication with members of the staff teaching and students. In conclusion, faculty members in the Faculties of Physical Education and Sports Sciences have an undesirable level of occupational pressure and a high level of stress when they use e-learning method of teaching. It is necessary that universities and colleges, when organizing the schedule and duties assigned to the faculty members who teach their students online, take care to reduce the burdens that lead to an increase of occupational pressures, as this has a negative impact on them.